Nanoelectronic device applications handbook - IEEE International Conference on Nanotechnology 2011 : Portland, Or.); Morris, James E. (Boca Raton, Fl. : CRC Press, 2013)
'The book has two purposes. First, it assembles the latest research in the field of nanoelectronics device technology in one place. Second, it exposes the reader to myriad applications that nanoelectronics devices technology has enabled. The book is meant for advanced graduate research work or for academicians and researchers. Contributed by world-renowned experts from academia and industry from around the globe, nanoelectronics devices will find widespread application range'--
Selected papers from the 11th IEEE International Conference on Nanotechnology held in Portland, Oregon, 15-19th August, 2011.
Includes bibliographical references and index.
Keywords: Nanoelectronics -- Congresses; Nanostructured materials -- Congresses